2003
DOI: 10.1007/s12055-003-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal nerve blockade versus thoracic epidural analgesia for post thoracotomy pain relief

Abstract: Background: Post thoracotomy pain is a major source of concern in the postoperative period. The purpose of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In summary, our study is in agreement with several previous studies [9,16,19]; however, other studies have found that intercostal block is a good alternative to thoracic epidural analgesia, as it is associated with similar pain scores and morphine consumption during the first 24 postoperative hours [4,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In summary, our study is in agreement with several previous studies [9,16,19]; however, other studies have found that intercostal block is a good alternative to thoracic epidural analgesia, as it is associated with similar pain scores and morphine consumption during the first 24 postoperative hours [4,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 93%
“…In a series of patients who underwent lung resection, forty cases with thoracic epidural or intercostal block pain relief therapy using 0.25% bupivacaine were compared. In this study, non-steroidal analgesic consumption and pain scores in the epidural group were significantly lower than in the intercostal group [19]. In a study by Concha et al [4] 16 patients (group 1) received a 5-segment intercostal block plus intravenous patient-controlled analgesia (PCA) morphine, whereas 15 patients (group 2) received PCA bupivacaine and fentanyl infusions through thoracic epidural catheters.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Sanjay et al . compared ICNB using 0.25% bupivacaine versus thoracic epidural analgesia for postthoracotomy pain relief and found that the effect of intercostal nerve block would wear off after 4 h.[ 10 ] Taylor et al . reported good quality analgesia for a median duration of 16 h with a significant reduction in morphine requirements with bupivacaine 0.375%.…”
Section: Discussionmentioning
confidence: 99%
“…ICNBs are generally administered as single injections at least two dermatomes above and below the thoracotomy incision [12].…”
Section: C)mentioning
confidence: 99%